Pengaruh Sikap Mengenai Bullying terhadap Perilaku Prososial Santri Bystander di Pondok Pesantren - Khoirotun Nisa, Luthfiah; Nurul Khasanah, Andhita (UNISBA Press, 2024)
Abstract. Islamic boarding schools are schools with the characteristic of teaching Islamic religious values. Adolescents who are in Islamic boarding schools will adapt or adjust themselves to various conditions within the scope of Islamic boarding schools. Cases of bullying in Islamic boarding schools are increasing because there are teenagers who become observers (bystanders) watching bullying incidents directly in front of their eyes which makes the perpetrators of bullying become reinforcements in carrying out bullying behavior. This research used a quantitative experimental method with a total of 344 MTS Islamic boarding school students in Bandung City as subjects. The measuring instrument used in this research uses the Attitude Scale which measures attitudes regarding bullying and the Prosocial Tendencies Measure (PTM) measuring instrument which measures prosocial behavior. The research results show that there is no influence of bullying attitudes on the prosocial behavior of Islamic boarding school observer students (Sig. 0.167 > 0.05). Abstrak. Pondok pesantren merupakan sekolah dengan ciri khas mengajarkan nilai agama islam. Remaja yang berada di pondok pesantren akan beradaptasi atau menyesuiakan dirinya dengan berbagai macam kondisi dalam ruang lingkup pondok pesantren. Kasus bullying di dalam pesantren semakin meningkat karena terdapat remaja yang menjadi pengamat (bystander) menonton kejadian bullying secara langsung di depan mata yang menjadikan pelaku bullying sebagai penguat dalam melakukan perilaku bullying. Penelitian ini menggunakan metode eksperimen kuantitatif dengan jumlah subjek 344 santri MTS pondok pesantren di Kota Bandung. Alat ukur yang digunakan dalam penelitian ini menggunakan Attitude Scale yang mengukur sikap mengenai bullying dan alat ukur Prosocial Tendencies Measure (PTM) yang mengukur perilaku prososial. Uji hipotesis dengan pengolahan data dilakukan dengan program SPSS. Hasil penelitan menunjukkan bahwa tidak terdapat pengaruh sikap mengenai bullying terhadap perilaku prososial santri pengamat pondok pesantren (Sig. 0,167 > 0,05).